PKM Pemberdayaan Kelompok Ibu Rumah Tangga Pemetik Daun Cincau Hijau Di Kelurahan Kresek Desa Tempurejo Kecamatan Pesantren Kota Kediri Melalui Program Bank Cincau - Samidjo, Samidjo; Santia, Ika; Prastaningtyas, Efa wahyu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Green grass jelly plants are one of the famous traditional medicinal plants in Indonesia. Called a medicinal plant because it is believed to be able to overcome hypertension and heartburn. One of these plant cultivation areas is in the Kresek Urban Village, Kediri City, East Java. The head of the green grass jelly cultivation group in the area started cultivating green grass jelly since 2011 with a land area of ​​100 square meters (m²), then distributed grass jelly seeds to several housewives in the Kresek village of Kediri City who had to retire early from one of the largest cigarette factories in the city Kediri with the aim of helping the economy of the group of housewives. But so far the cooperation system has only been limited to buying and selling between members to the chairman in small numbers. Constraints faced by these groups include: 1) lack of land for planting green grass jelly plants because once harvested, cincau leaves will be harvested again at the next 3-4 weeks, and 2) management of buying and selling cincau that has not been effective so that the cincau leaves with request so often leaves are rotten or unable to fulfill orders. Therefore, some solutions are needed including the solution that can be proposed for the group above is the "bank cincau" program. The Cincau bank program is an integrated collaboration system where several activities include: 1) mass seeding of cincau leaves in the area of ​​Kediri Kresek, 2) development of the cincau leaf storage system and marketing of cincau leaves, and 3) development of cincau leaf production technology ready for sale to develop a marketing system as well as the economic level of a group of housewives in the City of Kediri Kresek.